Investigation of temperature-driven ferroelectric phase-transition via modified Heisenberg model: The Monte Carlo simulation - Sittidet Srinoi (2018)
This work studies the temperature-driven ferroelectric phase-transition of ferroelectric polarization under the absence of electric field. The modified Heisenberg model in three dimensions was considered and simulated via Monte Carlo simulation. The Metropolis algorithm and the periodic boundary condition were employed. The dependence of electric polarization on temperature was investigated to define the ferroelectric phases and their structural phase transitions. From the results, with well-defined set of relevant temperature parameters, the phase-dependent polarization-behavior was found with a sudden change in its behaviors at the transition points. The structure factors were also considered and supported these phase changes. This conclusively pinpointed the important of temperature-dependent parameters in modeling ferroelectric materials. © (2013) Trans Tech Publications, Switzerland.